Synthesis of 14H-dibenzoxanthenes in green media using Sn(II)/nano silica as an efficient catalyst - Tavakol, Hossein; Firouzi, Mahdieh (Frontiers in Chemistry, 2022)
In this project, Sn(II)/nano silica has been prepared using a simple deposition of SnCl2.2.H2O on nano-silica. The prepared catalyst has been used as a green and reusable catalyst for synthesis of 14H-dibenzoxanthenes through a one-pot condensation reaction of β-naphthol with various aliphatic and aromatic aldehydes. Several xanthene derivatives have been synthesized using ethanol as the solvent, 10 mol percent of the catalyst, at reflux condition, in 3 h, and by 48%–94% yield. The structures of the synthesized derivatives are confirmed by melting point, FT-IR, 13C-NMR, and 1H-NMR analyses. Additionally, the nanocatalyst composition was confirmed by SEM, EDX, FT-IR, and XRD.